Government use licenses in Thailand: The power of evidence, civil movement and political leadership - Oh Cecilia; Chokevivat Vichai; Wibulpolprasert Suwit; Yamabhai Inthira (BMC, 2011)
Abstract This paper attempts to describe and analyse the policy processes that led to the granting and implementation of the government use licenses to enable the import and production of generic versions of medicines patented in Thailand. The decision to grant the series of government use licenses was taken despite much domestic and international controversy. The paper demonstrates that the policy processes leading to the granting of government use licenses are a successful application of the concept of "the triangle that moves the mountain". This is a well-known conceptualisation of a philosophical and strategic approach to public policy advocacy in Thailand, which propounds that the effective bridging of three powers; a.) Knowledge and evidence generated by research and analysis, b.) Civil society movements and public support, and c.) Leadership of policy makers and politicians; in a synergistic "triangle" can move "mountains", meaning the resolution of seemingly insurmountable problems. The paper provides insights into the policy context for the decision and analyses the roles of key actors, their motivations and the policy processes in the country.